Effect of educational program on improving knowledge and practice for adolescences with type 1 diabetes - Abolwafa, Nagat F.; Ahmed, Sanaa M.; Aly, Sahar A. (International Journal of Advanced Nursing Studies, 2017)
Background: Diabetes mellitus (DM) is one of the most common endocrine and metabolic conditions in childhood.Objectives: to determine the effect of educational program on the adolescences children knowledge and reported practices with type 1 diabetes.Method: Design pretest -posttest design was utilized to conduct this study.Setting: study was conducted at outpatient clinic for diabetes at Minia University Hospital for Obstetrics and Pediatrics.Sample: 50 adolescences children with type 1 diabetes.Tools: Pre-designed questionnaire sheet and Educational and training program.Results: this study showed significant improvement in adolescences knowledge and reported practices in post/test I and II.Conclusion: after the implementation of the program, there was remarkable improvement of adolescences children knowledge and reported practices.Recommendations: a developed program should be applied and repeat again every 6 months in the same study setting and adopted in other similar settings with required modifications, provision of continuing education programs.